Charge Extraction in Flexible Perovskite Solar Cell Architectures for Indoor Applications – with up to 31% Efficiency. (27th July 2022) - Teixeira, Cristina; Spinelli, Pierpaolo; Castriotta, Luigi Angelo; Müller, David; Öz, Senol; Andrade, Luísa; Mendes, Adélio; Carlo, Aldo Di; Würfel, Uli; Wojciechowski, Konrad; Forgács, Dávid
Abstract: Perovskite Solar Cells (PSCs) are well known for their high efficiencies under 1 sun (AM1.5G), however, PSC can also generate power by harvesting the low‐light available indoors. Here, three flexible PSC architectures are presented for indoor applications: with a metal electrode aiming for high efficiency; carbon electrode aiming for high stability and compatibility with large‐scale production; and hole transport material (HTM)‐free carbon for simplifying the fabrication process. A maximum efficiency of 30.9% (30.0%) under 1000 lux (200 lux) is obtained for a PSC with gold electrode. A maximum efficiency of 25.4% (24.7%) and 23.1% (22.3%) is obtained for the carbon devices with and without HTM, respectively, under 1000 lux (200 lux). To the best of the author's knowledge, the efficiency values presented here for a device with a carbon‐based electrode, with and without HTM, are the record values for a flexible PSC at indoor light conditions. Furthermore, the HTM‐free carbon device kept 84% of its initial efficiency after 1000 h at MPPT and lost virtually no performance after 1000 h at 85 °C. Also, non‐encapsulated devices of all configurations withstood 1600 h in air with a maximum loss in efficiency of 6%. Abstract : A flexible perovskite solar cell for indoor applications is fabricated. A record efficiency of 31% and 25%, and 23% at 1000 lux (393.6 W cm −2 ) is obtained for a device with an electrode of metal, carbon and carbon with no hole extraction layer, respectively. Carbon devices lost only 20% of its initial efficiency after 1000 h under Maximum Power Point Tracking.